2020
DOI: 10.1515/cclm-2020-0309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a turbidimetric C-reactive protein assay to monitor early-onset neonatal sepsis in South Kivu (Democratic Republic of the Congo)

Abstract: ObjectivesNeonatal sepsis, a condition defined as bacteremia within the first month of life accompanied by signs of systemic infection, is the most preventable cause of infant mortality in sub-Saharan Africa. Despite the development of new infection markers, C-reactive protein (CRP) is the most extensively studied acute phase reactant so far and the preferred index in many neonatal intensive care units (NICUs). The aim of the present study was to evaluate an affordable, non-commercial turbidimetric CRP assay f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Most of the literature define EOS being within the first 72h of life, especially for pre-term neonates, 20 however there are studies that use the value of the metric at either 48h, 21 , 22 or <7 days, 23 especially for term neonates. 20 , 24 Neonates born at term have a lower risk of neonatal sepsis compared to premature (<37 weeks gestational age), very low birth weight (VLBW, <1500g), or extremely low birth weight (ELBW) neonates. 25–27 A lack of clarity with neonatal sepsis definitions may bias and cloud data comparisons.…”
Section: Epidemiology Of Neonatal Sepsis In Lmics: a Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the literature define EOS being within the first 72h of life, especially for pre-term neonates, 20 however there are studies that use the value of the metric at either 48h, 21 , 22 or <7 days, 23 especially for term neonates. 20 , 24 Neonates born at term have a lower risk of neonatal sepsis compared to premature (<37 weeks gestational age), very low birth weight (VLBW, <1500g), or extremely low birth weight (ELBW) neonates. 25–27 A lack of clarity with neonatal sepsis definitions may bias and cloud data comparisons.…”
Section: Epidemiology Of Neonatal Sepsis In Lmics: a Summarymentioning
confidence: 99%
“… 31 Many global estimates are limited to inclusion of data from a relatively small number of countries, not an accurate representation of global incidence, more a biased reflection on available data, with scarcity of data from a large quantity of LMICs. However, from the data available, the incidence of EOS (and all neonatal sepsis; some studies include pooled metrics and/or variations in the definition of EOS) is considerably lower in HICs compared to LMICs; the NeonIN study collated data from 30 neonatal units in the UK and reported an EOS incidence of 0.7 cases per 1000 live births, 24 similar to EOS rates reported from studies in America between 0.5–0.8 cases per 1000 live births. 32–35 Comparably, a study from Norway reported EOS incidence of 0.97/1000 live births between 1996–2018.…”
Section: Epidemiology Of Neonatal Sepsis In Lmics: a Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Submicroscopic Plasmodium parasitemia was defined as a negative thick smear with a positive LAMP illumigene malaria assay. C-reactive protein (CRP) was measured by turbidimetric method as described elsewhere [24,25] using UVmini-1240 UV-VIS spectrophotometer (Shimadzu corporation, Japan). A direct colorimetric test without deproteinization of sample based on the 5-Br-PAPS method was used to measure serum zinc with the CYANSmart® spectrophotometer using zinc Spinreact color 5 Br-PAPS (Santa Coloma, Spain).…”
Section: Blood Collection and Laboratory Testsmentioning
confidence: 99%
“…Clinical chemistry analyzers based on turbidimetric principles are used in large clinical settings, while commercially approved ELISA kits are preferred in dispersed and remote settings [ 9 ]. In the present study, the Mindray BC-5390, Mindray BC-6800, and Johnson Vitros5600 analyzers were based on the principle of the turbidimetric method to detect CRP value [ 10 , 28 ]. The difference was that the Mindray analyzers used immunity transmission turbidity, while the Johnson Vitros5600 analyzer used immune scatter turbidity.…”
Section: Discussionmentioning
confidence: 99%